Սուրբ Ներսէս Շնորհալու «Բան մաղթանաց» ստեղծագործութիւնը - Ավագեան, Տ. Նարեկ վրդ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье речь идет о стихотворном произведении Св. Нерсеса Шнора- ли «Слово пожеланий», где начальные буквы первых строчек воспроизводят армянский алфавит. Нравоучительные произведения Святого Нерсеса Шнорали, написанные буквами армянского алфавита, имеют особую цель. Во-первых, представить буквы армянского алфавита словами, хорошо запоминающимися и начинающимися этими буквами. Во-вторых, этими буквами создавать произведения, имеющие определенный сюжет. The article refers to the poetic work entitled “Words of Prayer” by St. Nerses the Graceful written with the acrostic of the Armenian alphabet. The educational-moral works written with the acrostic of the Armenian alphabet by St. Nerses the Graceful have a certain purpose: 1. to introduce the letters of the Armenian alphabet with words beginning with those letters and being imprinted in the memory; 2. to create works with a certain plot development with those letters.
Keywords: Կրօնագիտութիւն; Literature